Dynamics of a flexible tethered satellite system in the presence of aerodynamic drag and gravity gradient - Aw, Aaron Teik Hong (2017)
Tethered Satellite System (TSS) has emerged as one of the main topics of discussion in the aerospace research field. However, most research works focus more on the rigid tether as compared to a flexible structure. In this thesis, three different material types utilized by a flexible tether are examined and compared with the common rigid tether. In addition, the air drag perturbation will be taken into consideration as the entire TSS is flown around the Low Earth Orbit (LEO) region where air-drag perturbation is a dominant factor. Subsequently, a survival analysis was performed. In addition, the gravitational force dynamic models as developed by Urrutxua, Peláez, and Lara are incorporated into the TSS model to analyze the stability for both rigid and flexible cases. Based on the numerical analysis, tungsten showed a better dynamic performance in terms of having the lowest hazard ratio reading, but Spectra-2000 showed to be the strongest in terms of tension performance, with a maximum tension force of 66 447 N and 43 298 N before snapping for a flexible tether in a non-coplanar model with and without drag, respectively. Albeit σ > 0.75, which exceeded the critical value, the TSS can be stabilized by varying the primary mass, M1, in an order of 1020 kg and the total tether length, L, under a specific condition. Nevertheless, the two-link flexible TSS is stabilized by utilizing the piecewise controllers and a total tether length of 700 m was deployed and maintained after a period of 450 seconds.